AB0419 Aurion Study: Preliminary Results of Voclosporin in Lupus Nephritis. (15th July 2016) - Yahya, R.; Gafor, A.H.B.A.; Huizinga, R.; Chan, T.M.; Solomons, N.
Abstract : Background: In lupus nephritis (LN), complete or partial remission (PR) is associated with better patient and renal survival. However, studies demonstrate that subjects who did not achieve a 25% reduction in proteinuria within 8 weeks of starting induction immunosuppression were unlikely to achieve even a PR. Recent studies suggest that a combination of calcineurin inhibitors (CNi's), MMF and low dose steroids may be effective in LN patients. Voclosporin (VCS) is a next generation CNi intended for the treatment of autoimmune diseases and prevention of transplant rejection, with a predictable pharmacokinetic-pharmacodynamic profile. An ongoing study (AURA-LV) is a global double-blind, prospective study comparing 2 doses of VCS with placebo. This study, AURION, is an exploratory study of VCS in active LN in combination with MMF and steroids. Objectives: The AURION study assesses the ability of biomarkers measured at 8 weeks to predict clinical response over 24 and 48 weeks. In addition complete remission is assessed at week 24, defined as a protein/creatinine ratio of ≤0.5 mg/mg and estimated glomerular filtration rate (eGFR, CKD-EPI equation) ≥60 mL/min/1.73 m 2 or no decrease from baseline in eGFR of ≥20%. Participating subjects with active lupus nephritis will take voclosporin 23.7 mg BID in combination with standard of care. We report preliminary biochemistry data. Methods: Eligibility criteria includes: renal biopsy within 2 years of screening; SLE by ACR criteria; laboratory features consistent with active LN; and eGFR >45ml/min/1.73m 2 . VCS 23.7 mg po BID is administered in combination with MMF 1–2g/day and a reducing course of corticosteroids. UPCr assessments are made at each visit, together with biomarker (C3, C4 and anti-dsDNA) data at regular intervals. Proteinuria reduction over time is presented for the first 7 subjects enrolled in this pilot study, together with renal function, C3, C4 and anti-dsDNA plots. To understand the impact of MMF/steroids alone, UPCr data is presented below with historical data from age/sex/UPCr matched patients from ALMS 1 . Results: (Mean±SD) Pretreatment UPCr was 2.5±1.6 mg/mg and eGFR was 115±34 ml/min. By week 8 mean UPCr had fallen to 0.5±0.5 mg/mg; a reduction in mean UPCr of 81%. eGFR at the same time-point was 113±10 ml/min. Expected increases in C3, C4 and decreases in anti-dsDNA were seen in this population. Conclusions: Preliminary data from this this pilot study indicates that MTT using VCS, in combination with MMF and steroids, produced consistent reductions in proteinuria with preservation of renal function in the first 7 subjects enrolled with active LN. The results of the confirmatory global AURA-LV study using similar treatment patterns will be available later this year. References: Appel GB, Contreras G, Dooley MA, et al. Mycophenolate mofetil versus cyclophosphamide for induction treatment of lupus nephritis. J Am Soc Nephrol. 2009 May;20(5):1103–12. Disclosure of Interest: R. Yahya Grant/research support from: Aurinia Pharmaceuticals, A. H. B. A. Gafor Grant/research support from: Aurinia Pharmaceuticals, R. Huizinga Shareholder of: Aurinia Pharmaceuticals, Employee of: Aurinia Pharmaceuticals, T. M. Chan Grant/research support from: Aurinia Pharmaceuticals, Consultant for: Aurinia Pharmaceuticals, N. Solomons Shareholder of: Aurinia Pharmaceuticals, Employee of: Aurinia Pharmaceuticals